Analisis terhadap Peraturan Daerah Provinsi Bali Nomor 2 Tahun 2012 tentang Kepariwisataan Budaya Bali serta Regulasi Terkait Dalam Menghadapi Permasalahan Wisatawan Asing - Khaliza, Ashila Raisya; Suhendra, Christabel Daniella; Parhusip, Naomi Inly; Dior, Valence Deanthony (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Foreign tourism is a strategic sector in the economic development of Bali Province. However, the continuous increase in the number of foreign tourists has also generated various challenges, particularly in relation to cultural preservation, environmental protection, and the lack of respect for local customs and values. This situation requires an active role from the local government through the formulation of regional regulations that are capable of regulating tourist activities in accordance with Balinese cultural principles. This study aims to examine the effectiveness of regional regulations in addressing issues related to foreign tourists in Bali Province, particularly in maintaining a balance between tourism-driven economic interests and the protection of local community interests. This study employs a normative legal research method using qualitative and descriptive analysis. The qualitative analysis is conducted through a statutory approach to the Regional Regulation of Bali Province Number 2 of 2012 concerning Balinese Cultural Tourism. The descriptive approach focuses on explaining the substance of the regulation, including the formulation and implementation of legal norms, as well as the scope of regulatory provisions applicable to foreign tourists. In this context, the regulation not only governs tourism activities but also emphasizes the protection and respect for cultural values and local norms in Bali Province. The findings indicate that, from a normative perspective, the regulation provides an adequate and comprehensive legal framework for the management of foreign tourism; however, its effectiveness continues to face challenges related to implementation, supervision, and law enforcement.